Effects of Psychotherapy on Quality of Life among Patients with Inflammatory Bowel Disease: A Systematic Review with Meta-Analysis - Subramaniam, Yashila; Ooi, Pei Boon; Hoo, Min Xi; Wong, Yin Yee; Phang, Kelly; Raja Ali, Raja Affendi; Pickup, Roger (Malaysian Journal of Medical Sciences, 2026)
Individuals diagnosed with inflammatory bowel disease (IBD) have been known to have diminished quality of life (QoL). This present study aimed to examine the impact of psychotherapy on the QoL of patients with IBD. A systematic search for studies was conducted through a total of six databases, namely, MEDLINE, PubMed, Scopus, SAGE, ProQuest (psychology database), and ProQuest (public health database) from their date of inception up to 20 March 2024. The inclusion criteria were studies on patients with IBD, carried out through a randomised controlled trial design, published in the English language, and with full-text content available online. Two researchers independently extracted articles that met the selection criteria and evaluated the quality of each study. A random-effects meta-analysis was conducted, and data were presented in weighted mean difference (WMD) with a 95% CI. Fourteen studies were included in the systematic review, of which three were included in the meta-analysis. Overall, while psychotherapy showed no significant improvements in some QoL domains such as clinical bowel condition and systemic symptoms, notable enhancements were observed in social functioning and overall QoL. The findings underscore the importance of integrating psychotherapeutic approaches into IBD management to address psychological and social challenges, thereby enhancing overall patient well-being. These results have significant implications for clinical mental health counsellors and future research in IBD care.